Biological Role of CDK 11 and 12 in Cell Cycle and its Function in Tumorigenesis - Danish Mohammad; Rida Tafveez; Zain JawedAbubaker; Shamim Mushtaq (ziauddin University, 2020)
Uninhibited proliferation and abnormal cell cycle regulation are the hallmarks of cancer. The main role of cyclin dependent kinases is to regulate the cell cycle and cell proliferation. These protein kinases are frequently down regulated or up regulated in various cancers. Two CDK family members, CDK 11 and 12, have contradicting views about their roles in different cancers. For example, one study suggests that the CDK 11 isoforms, p58, inhibits growth of breast cancer whereas, the CDK 11 isoform, p110, is highly expressed in breast tumor. Studies regarding CDK 12 show variation of opinion towards different parts of the body, however there is a consensus that upregulation of cdk12 increases the risk of breast cancer. Hence, CDK 11 and CDK 12 need to be analyzed to confirm their mechanism and their role regarding therapeutics, prognostic value, and ethnicity in cancer. This article gives an outline on both CDKs of information known up to date from Medline, PubMed, Google Scholar and Web of Science search engines, which were explored and thirty relevant researches were finalized.